"When Surviving Jim Crow Is a Preexisting Condition": The Impact of COVID‐19 on African Americans in Late Adulthood and Their Perceptions of the Medical Field. Issue 2 (10th October 2021) - Mingo, Taryne M.
Abstract : This article examines how the trauma of historical and structural racism affects one's health and well‐being across the life span, specifically for African Americans identified as descendants of Africans enslaved in the United States (DAEUS). Counselors are provided with antiracist strategies to support the intersection of multiple social identities for DAEUS citizens in late adulthood disproportionately affected by COVID‐19.